The Use of Digital Public – Relations in the Work of Iraqi Universities: A Survey Study of the Workers in the Departments of Public Relations - Mohammad, Sabah Anwar (ALBAHITH ALALAMI, 2017)
the digital public relations aim at make the workers getting the necessary information about the governmental institutions where they work and the enveronment surrounding them. it also tries to let the workers get the special knowlege of tthe publich relations and their jobs like the works of planning , arranging the active communication and executive skills needed in their writing , editing , special art skills for designing , production and technological skills to deal with the computer. the problem of the research includes some questions as : 1- what are the uses achieved by degetal public relations workers at Iraqi universities (Baghdad, Mustansiriya, and Iraqi) 2- what are the tools used to apply digital public relations in active communication at Iraqi universitites?The goals of the research are as follows:Identifying the extent to which employees use digital public relations according to the theory of uses and saturation .identifying the extent to which employees’ dependence on the tool of applying digital public relations the researcher ends with the following conclusions:1- the number of male respondents are larger than the females. their age is abut 20 years up to 30 years old . the educational level of the respondents who have bahelor degree are larger than those who have higher degrees. The university of Baghdad is higher in the number of workers in the departments of digital public relaions.2- the number of those who know how to use the internet and computer system increases in number year after another.